The assessment of aortic coarctation among the childrens population in Lviv region - A.А. Malska (Danylo Halytsky Lviv National Medical University, 2020)
Aim. To determine the rate of aortic coarctation, the correlation of its anatomical forms - critical and not critical, and the frequency of combination with the associated pathology; to define the features of the clinical course of its different anatomical forms; and to analyze the remote results of the surgical correction of this defect.